Analisis Potensi Produksi Enzim Amilase oleh Beberapa Species Bacillus serta Penentuan Aktivitasnya secara Kualitatif dan Kuantitatif - Geliz Luh Titisari; Nurul Haviza; Aken Putri Nandi Nanti; Syafrizayanti syafrizayanti; Prima Fitria Hillman (Departemen Kimia Universitas Andalas, 2026)
This study aimed to analyze the potential of several Bacillus species—Bacillus subtilis, Bacillus thuringiensis, and Bacillus cereus—in producing amylase enzymes and to determine their enzymatic activity both qualitatively and quantitatively. Screening was conducted using starch agar medium, where the formation of clear hydrolysis zones indicated amylase activity. Growth curve analysis was used to determine the optimal harvesting period based on the bacterial growth phase. Enzyme production was carried out in a nutrient medium containing starch, and the crude enzyme extract was tested for activity using the Somogyi–Nelson method. The results showed that all Bacillus species tested exhibited amylolytic activity, with B. subtilis showing the highest amylolytic index (1.97). However, B. cereus demonstrated the greatest enzymatic performance, with an enzyme activity of 0.219 U/mL and a specific activity of 8.193 U/mg protein. These findings indicate that B. cereus possesses strong physiological and genetic potential to produce high levels of extracellular amylase compared to B. subtilis and B. thuringiensis. Therefore, B. cereus can be considered a promising candidate for industrial amylase production, and further optimization of fermentation conditions is suggested to enhance enzyme yield and catalytic efficiency.